Availability and quality of cause-of-death data for estimating the global burden of injuries - Kavi Bhalla; James E Harrison; Saeid Shahraz; Lois A Fingerhut (The World Health Organization, 2010)
OBJECTIVE: To assess the availability and quality of global death registration data used for estimating injury mortality. METHODS: The completeness and coverage of recent national death registration data from the World Health Organization mortality database were assessed. The quality of data on a specific cause of injury death was judged high if fewer than 20% of deaths were attributed to any of several partially specified causes of injury, such as "unspecified unintentional injury". FINDINGS: Recent death registration data were available for 83 countries, comprising 28% of the global population. They included most high-income countries, most countries in Latin America and several in central Asia and the Caribbean. Categories commonly used for partially specified external causes of injury resulting in death included "undetermined intent," "unspecified mechanism of unintentional injury," "unspecified road injury" and "unspecified mechanism of homicide". Only 20 countries had high-quality data. Nevertheless, because the partially specified categories do contain some information about injury mechanisms, reliable estimates of deaths due to specific external causes of injury, such as road injury, suicide and homicide, could be derived for many more countries. CONCLUSION: Only 20 countries had high-quality death registration data that could be used for estimating injury mortality because injury deaths were frequently classified using imprecise partially specified categories. Analytical methods that can derive national estimates of injury mortality from alternative data sources are needed for countries without reliable death registration systems.